The Level Of Use Of Modern Information Technologies Today, Their Role In Data Collection, Diagnosis And Treatment In Various Areas Of Medicine - Mukaddas Valisherovna Urinova (Euro Asian Journal Publishing, 2024)
the article examines the level of use of modern information technologies today, their role in data collection, diagnosis and treatment in various fields of medicine.
Keywords: level; modern; use